CONSTRUCTION OF ARAB ETHNIC IDENTITY IN MEDAN - Yansari, Hanipa; Hidayat; Baiduri, Ratih (Universitas Negeri Medan, 2025)
This article was written to understand the construction of Arab ethnic identity in the city of Medan regarding various aspects of social life which manifest in educational, economic, social, political and religious issues. Of course, the focus of this research also does not ignore the history of ethnic Arabs migrating to the city of Medan and the motives driving them to migrate, either from the spread of Islam or for their economic prosperity. This research is qualitative in nature with an ethnographic writing approach. The results of the research show that Arab ethnics, in this case, construct their identity from their various social lives, in terms of education, economics, social life and politics, as an instrument to fight for and defend the religion they believe in, Islam, amidst the diverse development of the city of Medan. The identity construction carried out by the Arab ethnic group builds a balanced cultural ecosystem in the city of Medan. So that the city of Medan does not become a city that seems very Christian or very Hindu or even Confucian or very Buddhist. But it still maintains the existence of Islam as an Arab ethnic identity in filling the miniature beauty of a diverse city frame. The whole thing is outlined in the history of Arab ethnic migration in the city of Medan and their social life in various educational, economic, social, political and religious aspects. Key words: Identity Construction, Arab Ethnicity, Medan